A review of treatment methods for insensitive high explosive contaminated wastewater - Fawcett-Hirst, William; Temple, Tracey; Ladyman, Melissa K.; Coulon, Frederic (Elsevier, 2021)
Insensitive high explosive materials (IHE) such as 3-nitro-1,2,4-triazol-5-one (NTO) and 2,4-dinitroanisole (DNAN) are increasingly being used in formulations of insensitive munitions alongside 1,3,5-trinitroperhydro1,3,5-triazine (RDX). Load, assembly and packing (LAP) facilities that process munitions produce wastewater contaminated with IHE which must be treated before discharge. Some facilities can produce as much as 90,000 L of contaminated wastewater per day. In this review, methods of wastewater treatment are assessed in terms of their strengths, weaknesses, opportunities and threats for their use in production of IHE munitions including their limitations and how they could be applied to industrial scale LAP facilities. Adsorption is identified as a suitable treatment method, however the high solubility of NTO, up to 16.6 g.L which is 180 times higher that of TNT, has the potential to exceed the adsorptive capacity of carbon adsorption systems. The key properties of the adsorptive materials along the selection of adsorption models are highlighted and recommendations on how the limitations of carbon adsorption systems for IHE wastewater can be overcome are offered, including the modification of carbons to increase adsorptive capacity or reduce costs.
Keywords: Wastewater treatment; NTO; DNAN; Insensitive high explosives; Adsorption